Association between Endothelial Cell Density and Corneal Thickness in Transplanted versus Normal Corneas: A retrospective cohort study - N. Tesavibul (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND. Objective: To investigate the association between endothelial cell density (ECD) and corneal thickness (CT) in patients with clear corneal grafts after penetrating keratoplasty (PKP) and compare the results with normal corneas. Materials and Methods: In the retrospective cohort study, the authors reviewed the medical charts of patients who underwent a PKP and whose grafts remained clear. Abnormal grafts such as those with irregular surfaces, central scarring, secondary guttae, and graft edema were excluded. The demographic data, ECDs, and CTs were recorded and compared with those of normal corneas. The ECDs were measured using corneal microscopy, and the CTs were measured by optical coherence tomography. Results: Ninety-six eyes treated with PKP and 86 normal eyes were enrolled. One hundred four women and 78 men were included with a mean age of 64.0±16.7 and 68.6±14.3 years in the PKP group and normal group, respectively. The mean time after PKP was 3.7±3.1 years (range 0.3 to 12.6 years). The mean CTs did not differ between the two groups, but the mean ECD in the PKP group was significantly less than in the normal group (1,109.2 versus 1,905.4 cells/mm2, p<0.001). The degree of polymegathism was significantly higher in the PKP group, while the degree of pleomorphism was significantly (p<0.001) lower compared to the normal group. Conclusion: When comparing eyes with the same CTs, those treated with PKP had lower ECDs, more polymegathism, and less pleomorphism than normal corneas.